1944
DOI: 10.1002/path.1700560214
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase production by staphylococci on a solid medium

Abstract: Many tests have been used to distinguish pathogenic from non-pathogenic staphylocooci ; the most useful, now generally acccpted, is the demonstration of coagulase. The coagulation of plasma by certain staphylococci was origina.lly described by Much (1908) and has been developed by many workers (Cruickshank, 1937 ; Fairbrother, 1940 ; and others). Recently Cadness-Graves et al. (1943) found that the clumping of staphylococci in plasma as determined by slide tests was roughly parallel to coagulase production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1947
1947
1984
1984

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Taylor and McDiarmid (18) used rabbit, sheep, and ox plasmas in the plate test. Numerous plating media have been prepared with human or rabbit plasmas (6,7,10,15,17). Duthie and Lorenz (6) reported that cow, sheep, dog, guinea-pig, and mouse plasmas exhibited a relative deficiency in coagulase-reacting factor (CRF), whereas the plasmas of man, monkey, horse, cat, pig, fowl, and rabbit contained substantially more CRF.…”
mentioning
confidence: 99%
“…Taylor and McDiarmid (18) used rabbit, sheep, and ox plasmas in the plate test. Numerous plating media have been prepared with human or rabbit plasmas (6,7,10,15,17). Duthie and Lorenz (6) reported that cow, sheep, dog, guinea-pig, and mouse plasmas exhibited a relative deficiency in coagulase-reacting factor (CRF), whereas the plasmas of man, monkey, horse, cat, pig, fowl, and rabbit contained substantially more CRF.…”
mentioning
confidence: 99%
“…The pour plate method along with tube a n d slide tests are the most common procedures for testing the production of coagulase by S. aureus (Boothby et al 1979). Penfold (1944) a n d Reid a n d Jackson (1945) inoculated the surface of a medium containing plasma with culture of staphylococci. Colonies of coagulase-positive staphylococci were differentiated by the surrounding coagulation zone.…”
Section: Pour Plate Methodsmentioning
confidence: 99%
“…aureus and Staph. albus in the clinical laboratory, since the whole plasma-containing solid media (Penfold, 1944;Lack, 1957;Esber and Faulconer, 1959) show false-positive reactions with coagulase-negative staphylococci (Williams and Harper, 1946;Klemperer and Haughton, 1957;Lotter and Horstman, 1967). These non-specific reactions appear practically eliminated in the medium of Klemperer and Haughton (1957) because of its low plasma content (3 %).…”
mentioning
confidence: 99%